2007
DOI: 10.1038/nature06305
|View full text |Cite
|
Sign up to set email alerts
|

Calcineurin sets the bandwidth for discrimination of signals during thymocyte development

Abstract: At critical times in development, cells are able to convert graded signals into discrete developmental outcomes; however, the mechanisms involved are poorly understood. During thymocyte development, cell fate is determined by signals originating from the α β T-cell receptor. Low-affinity/avidity interactions between the T-cell receptor and peptide-MHC complexes direct differentiation to the single-positive stage (positive selection), whereas highaffinity/avidity interactions induce death by apoptosis (negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 28 publications
0
58
1
Order By: Relevance
“…By analogy with T cell development (49), enhanced positive selection of lower affinity iNKT cells might also be caused by increased intracellular signaling. Intracellular signaling during iNKT cell selection and development could potentially be perturbed in the absence of Fra-2, likely via the dysregulation of AP-1 target genes evident from our microarray data; this could then affect the selection process.…”
Section: Discussionmentioning
confidence: 99%
“…By analogy with T cell development (49), enhanced positive selection of lower affinity iNKT cells might also be caused by increased intracellular signaling. Intracellular signaling during iNKT cell selection and development could potentially be perturbed in the absence of Fra-2, likely via the dysregulation of AP-1 target genes evident from our microarray data; this could then affect the selection process.…”
Section: Discussionmentioning
confidence: 99%
“…The RasGEF activity of RasGRP1 in the Golgi depends both on DAG and on increased intracellular Ca 2+ concentration [22]. RasGRP1 is barely expressed in thymocytes at the double-negative (CD4 − CD8 − , DN) to double-positive (CD4 + CD8 + , DP) stages [24]; instead, the calcineurin/ NFAT pathway was shown to modulate Ras activation in CD4 + CD8 + CD69 − DP thymocytes that have not yet undergone positive selection, altering the threshold for ERK activity and allowing weak TCR signals to induce positive selection [25]. B-Raf, MEK and ERK activation are all impaired in DP thymocytes from mice lacking the calcineurin regulatory subunit CnB1, suggesting that calcineurin/ NFAT-dependent transcription regulates the Raf/ Ras/ MAP kinase pathway at several levels, both upstream and downstream of Raf.…”
Section: Integration and Crosstalk Between Ca 2+ And Other Signallingmentioning
confidence: 99%
“…Moreover, over the last few years, multiple studies have demonstrated the regulation of signaling strength in the immune system. Studies in T cells and macrophages have revealed that calcineurin (which acts through an unknown mechanism), miR-181 and miR-155 (which regulate the translation of phosphatases, thereby affecting inhibitory signaling) all function to modify the signaling strength of ligand engagement on the cell surface (Gallo et al, 2007;Li et al, 2007;O'Connell et al, 2009). Obviously, the ability to manipulate signaling strength or response thresholds may be excellent targets for future clinical intervention, such as inducing tolerance.…”
Section: What Can We Learn From Allorecognition In Non-vertebrates?mentioning
confidence: 99%